EFFECT OF FEEDER WITH AQUAENZYM OF DIFFERENT FREQUENCY ON GROWTH AND SURVIVAL RATE OF RED TILAPIA (Oreochromis sp) WITH BIOFLOK SYSTEM - Dwi Muhammad Lutfi; Mulyadi Mulyadi; Iskandar Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRAKThis research was conducted from July to Agustus 2019 in the Technical Services Unit (UPT) Pool and Hatchery, Faculty of Fisheries and Marine Affairs, Riau University, Pekanbaru. The purpose of this rate determine the frequency of feeding with aquaenzyme for the growth and survival of red tilapia (Oreochormis sp) with a biofloc system. The method used in this study is the experimental method using a Completely Randomized Design (CRD) of 1 factor with 4 levels of treatment and 3 replications. P1 : Frequency of feeding 2 times/day P2 : Frequency of feeding 3 times/day P3 : Frequency of feeding 4 times/day P4 : Frequency of feeding 5 times/day.The results showed that the best treatment was P2: frequency of feeding 3 times a day. Absolutegrowth weight was 10.86 grams, absolutegrowth length was 3.60 cm, specific growth rate was 3.53%, feed efficiency was 95.43%, survival rate (SR) was 91 %, water quality parameters temperature is 26-300 ͦ C, dissolved oxygen is 5.20-6.15 Keywords: Frequency,Aquaenzyme,Red Tilapia (Oreochromis sp)